Effectiveness analysis of antipsychotics in schizophrenia using psychometric scales: an observational study - Agrawal, Ratna; Rath, Bhabagrahi; Shukla, Rajni Kant; Mohapatra, Sabita (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Schizophrenia is a commonest and one of the well known psychiatric disorders. Life expectancy of a patient with schizophrenia may be 20 to 30 years shorter than the general population. Long term antipsychotic therapy is usually required for the management of schizophrenia. It is not currently possible to predict which antipsychotic may be optimal for a given patient because there are still many debates about effectiveness and efficacy of atypical drugs over first generation antipsychotics. So, our aim is to assess the effectiveness of various antipsychotics by using various psychometric scales, which will be helpful to bring out better treatment options for schizophrenia patients. Methods: This was an observational questionnaire based study, conducted on patients of inpatient and outpatient Department of Psychiatry and Department of Pharmacology at VIMSAR, Burla, for a period of 24 months (September 2015 to August 2017). Patients of schizophrenia aged 18 years or above were subjected to clinical global impression – severity scale (CGI-S) and clinical global impression – improvement scale (CGI-I) questionnaire after taking informed consent. Then scores were calculated using non parametric test with Graph pad Prism version 6.0. Results: Out of the 90 cases, majority (60) of patients belonged to the middle (25 to 45 yrs) age group followed by 20 younger (<25 yrs) age group and rest 10 were elderly (>45 yrs) patients. Both scales showed significant improvement with atypical antipsychotics as compared to first generation antipsychotics. Conclusions: Based on these findings, we can conclude that atypical antipsychotics are more effective than first generation antipsychotics. But further studies are needed to assist clinicians in making optimum treatment decisions.